Effect of feeding protected protein on productive performance in dairy cows - HALOI, SIKHAMONI; BHUYAN, ROBIN; SAIKIA, BIBEKA NANDA; BORAH, LAKHYAJYOTI; TALUKDAR, PAPORI; BARUAH, ANUBHA; BORA, JOGI RAJ; TAMULY, SHANTANU; HUSSAIN, JAKIR; SRIHITHA, SALUR; DIXIT, CHANDRA PRAKASH (The Indian Journal of Animal Sciences, 2025)
An experiment was conducted on lactating crossbred cows for assessing feeding effect of heat treated (HTSBM) and formaldehyde treated (FTSBM) soybean meal on productive performance of crossbred cows. Untreated soyabean meal (UTSBM) served as control group and HTSBM and FTSBM as treatment groups. Feeding of roughage and concentrate mixture having soybean meal (untreated) was offered in UTSBM group; while concentrate mixture with heat treated and formaldehyde treated soybean meal was offered to HTSBM and FTSBM group, respectively (n=8). Results showed that feeding HTSBM and FTSBM did not have significant effect on average dry matter (DM) intake (kg/Day) of cows. The cows fed HTSBM and FTSBM diets had a higher dry matter (P<0.05) and crude protein (P<0.01) digestibility than cows fed UTSBM diet. However digestibility of all other nutrients did not differ significantly among groups. Heat and formaldehyde treatments reduced (P<0.01) rumen degradable protein and increased (P<0.01) undegradable dietary protein in soybean meal. The average daily milk yield and fat corrected milk yield (kg/Day) was significantly higher (P<0.01) in HTSBM (9.01 ± 0.14 and 9.42 ± 0.17) and FTSBM (8.93± 0.14 and 9.30 ± 0.18) groups compared to UTSBM (7.70 ± 0.98 and 8.12 ± 0.16) group. The milk parameters like fat, protein, lactose, total solid and solid not fat did not differ significantly among groups. The feed cost per kg of milk was lower in HTSBM and FTSBM groups compared to UTSBM group.